USING OF THE YOUTUBE AS A LEARNING TOOL FOR KINDERGARTEN STUDENTS - Elisa Oliveira Fernandes Xavier (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
The main purpose of my session is to share my best practices in using of YouTube as a learning tool for kindergarten students, which the author has used to facilitate her English teaching and learning activities in a Private school in Dili, Timor-Leste. YouTube provides various educational materials, such as videos, animations, songs, animated movies, and interactive content, that support kindergarten learners in practicing and developing their vocabulary, pronunciation, and listening skills through enjoyable learning activities. The integration of colourful visuals and interesting audio materials helps students create more enjoyable learning environments that enhance their attention, interest, motivation, and participation during classroom learning activities. In addition, YouTube assists teachers in developing innovative teaching and learning activities that strengthen kindergarten students’ language development. This technological learning tool is easily accessible to both teachers and students and can be applied in school settings, as well as outside the classroom or at home, to support online learning activities. My session will benefit kindergarten students, parents, and educators who are interested in applying YouTube creatively and effectively to improve English language learning activities for kindergarten students.